Annotated list of pteridophytes of the State of Mexico, Mexico - Tejero-Díez, J. Daniel; Arreguín-Sánchez, Ma. de la Luz (Instituto de Ecología, A.C., 2005)
248 pteridophyte species and subspecific taxa are recorded for the state of Mexico, including 60 new state records and two new species. Specific and infraspecific taxa are accompanied by information regarding distribution world-wide and within Mexico and the state of Mexico, as well as life form, habitat, vegetation type, and altitudinal range within the study area.